Direct Instruction and Higher-Order Thinking Skills: Evidence from the Merdeka Curriculum Implementation - Nur Amalina; Wan Hasmah Laili Binti Wan Hamat (CV Najmi Edu Creative, 2026)
This study reviews the effectiveness of Direct Instruction in enhancing Higher-Order Thinking Skills (HOTS) during the implementation of the Merdeka Curriculum in secondary schools in Pekanbaru. The research was conducted from August to December 2025 using a quantitative quasi-experimental design involving 128 students divided into experimental and control groups. The experimental group received Direct Instruction integrated with HOTS-oriented tasks, while the control group experienced conventional instruction. Data were collected through validated HOTS assessment instruments covering analysis, evaluation, and creation domains. Statistical analysis used independent-samples t-tests and effect-size analysis. The results showed that the experimental group achieved a significantly higher mean score (M = 84.67, SD = 6.21) than the control group (M = 76.14, SD = 7.03), with t(126) = 7.18, p < .05, and a large effect size (Cohen’s d = 0.87). The evidence suggests that structured explanation, guided practice, and immediate feedback effectively support students’ analytical reasoning and analytical problem-solving skills in the implementation of the Merdeka Curriculum. The findings also suggest that explicit instructional approaches remain compatible with Higher-Order Thinking Skills (HOTS)-oriented learning when combined with cognitively demanding activities and systematic instructional scaffolding.